HUBUNGAN ANTARA PEMBELAJARAN DARING DENGAN KEMANDIRIAN BELAJAR SISWA SELAMA PANDEMI COVID-19 - Alfatia Amini; Teguh Prasetyo; Resti Yektyastuti (SITTAH: Journal of Primary Education, 2022)
The COVID-19 pandemic has changed the implementation of learning from face-to-face to virtual. This study aims to determine the relationship between online learning and student learning independence at the State Elementary School (SDN) Lanbau 02 Citeureup, Bogor Regency, West Java. The research method used is quantitative with correlation techniques. Data collection was obtained through a questionnaire to 63 students as respondents. The result of this research is that the calculated r-value is 0.540, and compared to the r table value of df 61 is 0.2091. So, the value of rarithmetic > rtable or 0.540 > 0.2091 indicates a relationship between online learning and student learning independence. This study concludes that there is a relationship between online learning and the learning independence of grade VI students at SDN Lanbau 02. This study suggests the need for collaboration between teachers and parents to develop students' independent learning attitudes during and after the COVID-19 pandemic.